(untitled) (Proceeding of SINERGY, 2026)
Rising public awareness of healthy eating has increased interest in gluten-free products. However, Teras Rayu, a gluten-free pastry and bakery business that also offers creative workshops, does not yet have a digital platform that can optimally present product information and workshop reservations. This study aims to design the UI/UX of the Teras Rayu application so that users can more easily find gluten-free products, place orders, and reserve workshops through a clear and user-friendly flow. The design process uses the Design Thinking method through the empathize, define, ideate, prototype, and test stages. The results are presented in the form of wireframes and a high-fidelity prototype that illustrate the user journey from browsing the catalog, ordering, and making payments to reserving workshops. The evaluation was conducted through usability testing using Maze, involving seven respondents and six task scenarios, achieving a success score of 82, which indicates that most users were able to understand the application flow well.